Co Design PA-Antenna for automotive radar with 79 GHz of frequency - BESSIKE, MOUSSA; Offolé Florence; NGUIYA Severin (IJRDO-Journal of Applied Science, 2021)
this research work proposes a transmitter unit composed of the antenna and the amplifier for the automotive radar application. As part of our work, we chose to design a printed rectangular patch antenna. We proceeded to the result of pre-dimensioning formulas and impedance matching techniques to the modeling of the patch antenna printed on a Rogers Duriod 5880 substrate of relative permittivity 2.2 and thickness 0.127 mm with the theory transmission lines. Then, after finishing the antenna design, we proceeded to the design of a field effect type transistor amplifier (FET). The amplifier design is also made with the same substrate used for the antenna design, to ensure the maximum power transfer between the antenna and the amplifier, we have designed a corresponding network. We use the following software for the implementation: CST-Microwave 2018 for the design of the antenna and ADS 2020 for the modeling of the amplifier and the Antenna-Amplifier block.